(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The development of new hypereutectic Al-Si alloys with increased mechanical and improved operational properties is an up-to-date engineering task. The non-standardized hypereutectic aluminum-silicon alloy AlSi18Cu3CrMn is modified with different modifiers (standard modifier P and a complex of modifiers P, Ti, B and Be). The compositions thus modified are subjected to heat treatment (T6). Artificial aging after quenching was carried out under different parameters (temperature and time). The aim of the present study is to determine the influence of the used modifiers on the corrosion rate of the compositions under the same conditions. The gravimetric method was used.